A submillimeter frequency multiplier. Part 1. Conditions of simultaneous two-mode excitation in the slow-wave structure of the o-type oscillator - Mil’cho, M.; Ilyenko, K. (Radiofizika i èlektronika, 2020)
Subject and Purpose. A special need for oscillators amenable to operation in the short-wave end of the submillimeter wave band sends us in search for new ways of their development. A proposal exists related to vacuum-tube frequency multipliers based on the backward-wave oscillator (BWO) or its variant, the clinotron. Sometimes a simultaneous excitation of two different-frequency oscillations is experimentally observed in ordinary millimeter wave clinotrons, orotrons and diffraction radiation oscillators. The aim of the present study is to examine whether those operational regimes can be implemented in the creation of electronic frequency multipliers in the submillimeter wave band. Methods and Methodology. The research method is a theoretical analysis of the process of simultaneous interaction of the electron beam with the electromagnetic fields of two modes in the BWO slow-wave structure. The aim is finding relationships to impose on the slow-wave structure parameters and the BWO operation figures and thus furnish a simultaneous excitation of the two modes. The obtained relationships are tested against published experimental results. Results. Two conditions of simultaneous mode excitations have been formulated, requiring (i) equal velocities of the operating spatial harmonics and (ii) their strict frequency multiplicity. Handy diagrams have been constructed, which made it possible to build frequency multiplication schemes with any multiplicity. The rigorous analytical method of comb dispersion calculation has been generalized to the higher passbands of large numbers. The calculation results have been compared with relevant experimental data, lending support to the validity of the obtained formulas to describe the frequency multiplication regime. Conclusion. A possibility has been theoretically shown of designing submillimeter vacuum-tube frequency multipliers upon clinotron-type oscillators with a single slow-wave structure. The regime of simultaneous generation of two given frequencies requires that the system dispersion in different passbands be controlled by moving a screen over the comb-type slow-wave structure.